Gluten enteropathy. Gluten-free raw material - Mukoid, Roman; Koshova, Valentina; Parkhomenko, Anastasia; Yakimenko, Lyudmila (My University, 2019)
The purpose of the work was to pick up the optimal conditions for the production of high-quality rice malt, as well as further analysis.
Keywords: целіакія; солод рисовий; пиво; затирання; безглютенова сировина; beer; mashing; gluten-free raw material; кафедра біотехнології продуктів бродіння і виноробства